2018
DOI: 10.1016/j.bbadis.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and branched-chain amino acid depletion during mouse preimplantation embryo culture programmes body weight gain and raised blood pressure during early postnatal life

Abstract: Mouse maternal low protein diet exclusively during preimplantation development (Emb-LPD) is sufficient to programme altered growth and cardiovascular dysfunction in offspring. Here, we use an in vitro model comprising preimplantation culture in medium depleted in insulin and branched-chain amino acids (BCAA), two proposed embryo programming inductive factors from Emb-LPD studies, to examine the consequences for blastocyst organisation and, after embryo transfer (ET), postnatal disease origin. Two-cell embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Therefore, differences in body weight confirmed a lower growth performance in VT animals, which agreed with previous studies carried out in rabbits undergoing VET [15,30,39]. Concordantly, previous studies have demonstrated that the nature of the preimplantation environment during ART can program development, affecting postnatal growth and phenotype [7,14,[45][46][47]. Notably, although the pattern of postnatal growth alteration in VT animals was similar in both sexes, males duplicated body weight differences between VT and NC compared to the females at the age of 20 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, differences in body weight confirmed a lower growth performance in VT animals, which agreed with previous studies carried out in rabbits undergoing VET [15,30,39]. Concordantly, previous studies have demonstrated that the nature of the preimplantation environment during ART can program development, affecting postnatal growth and phenotype [7,14,[45][46][47]. Notably, although the pattern of postnatal growth alteration in VT animals was similar in both sexes, males duplicated body weight differences between VT and NC compared to the females at the age of 20 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…All data analyses from the embryo studies were analyzed in parallel by a multilevel random effect regression model (Table S2) which takes into account the hierarchical nature of the data considering between‐dams and between‐litter variations and the different parameters measured from individual embryos including number of cells, gene expression, and immunofluorescence. This regression model accounting for embryo number has been widely used previously (Kwong et al, 2004; Velazquez et al, 2018; Watkins et al, 2007, 2010, 2011; Watkins, Ursell, et al, 2008; Watkins, Wilkins, et al, 2008; C. L. Williams et al, 2011). Both ANOVA (reported in tables and figures in main manuscript) and the multilevel regression model (Table S2) gave similar results.…”
Section: Methodsmentioning
confidence: 99%
“…This regression model accounting for embryo number has been widely used previously (Kwong et al, 2004;Velazquez et al, 2018;Watkins et al, 2007Watkins et al, , 2010Watkins et al, , 2011Watkins, Ursell, et al, 2008;C. L. Williams et al, 2011).…”
mentioning
confidence: 99%
“…Insulin and BCAAs are potent activators of the mTOR signalling pathway regulating cellular growth (Wang & Proud 2009) and, as a consequence of dietary-induced reduction in these metabolites, blastocyst mTOR activity is reduced by Emb-LPD (Eckert et al 2012). This early maternal-embryo interaction is critical since it activates later adverse programming as shown both by an in vitro culture model in medium reduced in insulin and BCAAs (Velazquez et al 2018) and by embryo transfer of Emb-LPD blastocysts into control, normal-fed, recipients (Watkins et al 2008).…”
Section: Maternal Undernutritionmentioning
confidence: 99%